The First 100 Days: Lessons from football. (2nd May 2021) - Denton, Phil
Abstract : Headteacher Phil Denton has spent the last 30 months talking to Premier League managers about the lessons we can draw from the high-pressure, unforgiving world of football management, especially when it comes to tackling the first 100 days in post…